2021
DOI: 10.1007/978-3-030-78334-1_9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Optimal Lockdown Strategies: The Effect of New and More Virulent Strains

Abstract: Most nations have responded to the COVID-19 pandemic by locking down parts of their economies starting in early 2020 to reduce the infectious spread. The optimal timing of the beginning and end of the lockdown, together with its intensity, is determined by the tradeoff between economic losses and improved health outcomes. These choices can be modelled within the framework of an optimal control model that recognises the nonlinear dynamics of epidemic spread and the increased risks when infection rates surge bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[11] includes the effect of social fatigue and endogenous treatment capabilities. [12][13][14] concentrate on the qualitative behavior of the solution and identify parameter regions where the optimal solution is qualitative stable. The parameter regions are separated by bifurcation curves where Skiba solutions or other interesting mathematical phenomena arise.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…[11] includes the effect of social fatigue and endogenous treatment capabilities. [12][13][14] concentrate on the qualitative behavior of the solution and identify parameter regions where the optimal solution is qualitative stable. The parameter regions are separated by bifurcation curves where Skiba solutions or other interesting mathematical phenomena arise.…”
Section: Plos Onementioning
confidence: 99%
“…The death rate is increasing in I due to the congestion effects of the health sector (for dramatic examples we refer to Lombardia in Italy or New York City both in spring 2020, or Brazil in spring 2021). Several contributions use a similar form, see e.g., [12][13][14]…”
Section: Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balancing the health and economic trade-offs of NPIs is crucial in resolving pandemicrelated problems, and the optimal impact of NPIs and optimal lockdown strategies have been dissected by various scholars (Tildesley et al, 2021;Caulkins et al, 2022;Acemoglu et al, 2020). A study by Tildesley et al (2021) revealed that precision in timing and strength of interventions is highly determined by the control's target: instituting an optimal level of control can lead to a decrease in net monetary loss, conditional on the precise willingness to pay per quality adjusted life year value.…”
Section: Introductionmentioning
confidence: 99%